Anti-Radicalism Literacy Jihad: Efforts to Contextualize Nahdlatul Ulama's Jihad Resolution in the Modern Era - Faizah, Rohmatul; Baedowi, Ahmad (Future Science, 2023)
The Nahdlatul Ulama Jihad Resolution, which was proposed as an effort to seize and defend the Unitary State of the Republic of Indonesia (NKRI) from the hands of colonialists, was based on the postulates of the Islamic religion which obliges every Muslim to defend the homeland and defend the independence of the Unitary State of the Republic of Indonesia. The jihad resolution that was proclaimed immediately spread widely to society. In today's context, jihad, which is interpreted as a serious effort, can be widened in scope in terms of protecting all of Indonesia's blood from threats and exposure from extreme and radical groups through strengthening literacy or literacy jihad. Nowadays Islamic boarding schools as educational institutions which are one of the strongholds of the Republic of Indonesia have undergone changes in responding to the challenges of the times by incorporating information technology knowledge. This knowledge is an effort to develop general knowledge as well as the practice of using Information and Communication Technology (ICT) to equip students in this digital era. This is an effort to contextualize NU's jihad resolution in the modern era, namely jihad in the field of literacy to ward off radicalism.